Stabilizer-Guided Inhibition of Protein-Protein Interactions - Milroy, Lech-Gustav; Bartel, Maria; Henen, Morkos A.; Leysen, Seppe; Adriaans, Joris M. C.; Brunsveld, Luc; Landrieu, Isabelle; Ottmann, Christian (Angewandte Chemie International Edition, 2015)
The discovery of novel protein–protein interaction (PPI) modulators represents one of the great molecular challenges of the modern era. PPIs can be modulated by either inhibitor or stabilizer compounds, which target different though proximal regions of the protein interface. In principle, protein–stabilizer complexes can guide the design of PPI inhibitors (and vice versa). In the present work, we combine X‐ray crystallographic data from both stabilizer and inhibitor co‐crystal complexes of the adapter protein 14‐3‐3 to characterize, down to the atomic scale, inhibitors of the 14‐3‐3/Tau PPI, a potential drug target to treat Alzheimer’s disease. The most potent compound notably inhibited the binding of phosphorylated full‐length Tau to 14‐3‐3 according to NMR spectroscopy studies. Our work sets a precedent for the rational design of PPI inhibitors guided by PPI stabilizer–protein complexes while potentially enabling access to new synthetically tractable stabilizers of 14‐3‐3 and other PPIs. The rational design of a protein–protein interaction inhibitor was guided by the co‐crystal structure of a protein–stabilizer complex and based on a non‐covalent tethering approach. The most potent inhibitor of the binding of 14‐3‐3 to phosphorylated full‐length Tau was biochemically and biophysically characterized and has a novel molecular structure that specifically targets the inhibitor–stabilizer interface of 14‐3‐3.